2012
DOI: 10.1159/000334913
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Self-Perception Period of Lower Urinary Tract Symptoms and the International Prostate Symptom Score

Abstract: Objectives: The timing of visiting a hospital after self-perception of lower urinary tract symptoms (LUTS) is different between individuals. The association between the self-perception period (S-PP) of LUTS and the progression of LUTS has seldom been documented. The aim of this study was to investigate the association between the S-PP of LUTS and the International Prostate Symptom Score (IPSS). Subjects and Methods: This was a cross-sectional study comprising 267 men aged 40 years and older who participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…The severity of BPH in men was measured using the IPSS, which is based on the AUA symptom index, with one additional question on QOL. Since the adoption of the IPSS questionnaire at an International Consultation on Benign Prostatic Hyperplasia organized by the World Health Organization, it has been translated into many different languages and adapted according to the circumstances of each country, and is now widely used for the objective assessment of LUTS . The Korean version of the IPSS was verified by Choi et al in terms of both its relevance and reliability, and it is now the most typical diagnostic instrument for LUTS in Korea…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of BPH in men was measured using the IPSS, which is based on the AUA symptom index, with one additional question on QOL. Since the adoption of the IPSS questionnaire at an International Consultation on Benign Prostatic Hyperplasia organized by the World Health Organization, it has been translated into many different languages and adapted according to the circumstances of each country, and is now widely used for the objective assessment of LUTS . The Korean version of the IPSS was verified by Choi et al in terms of both its relevance and reliability, and it is now the most typical diagnostic instrument for LUTS in Korea…”
Section: Methodsmentioning
confidence: 99%
“…Since the adoption of the IPSS questionnaire at an International Consultation on Benign Prostatic Hyperplasia organized by the World Health Organization, 17 it has been translated into many different languages and adapted according to the circumstances of each country, and is now widely used for the objective assessment of LUTS. 3,18,19 The Korean version of the IPSS was verified by Choi et al in terms of both its relevance and reliability, and it is now the most typical diagnostic instrument for LUTS in Korea. 20 The IPSS questionnaire consists of eight items, which include seven 6-point scale questions about symptoms (residual urine sensation, urinary frequency, interrupted stream, urinary urgency, weak urinary stream, urinary hesitancy and nocturia) and one 7-point scale question on the patient's satisfaction with their urinary condition.…”
Section: Ipss Questionnairementioning
confidence: 96%
See 1 more Smart Citation
“…In reality, however, the timing of hospital visits for medical treatment after perceiving OAB symptoms differs between individuals. Moreover, our preliminary survey of LUTS self‐perception showed that the self‐perception period of LUTS affects the International Prostate Symptom Score (IPSS) independently of age (9). One important motivation for this study arose from the need to overcome data scarcity and substantiate general opinions regarding OAB symptoms from a health sciences perspective.…”
Section: Introductionmentioning
confidence: 99%
“…It develops slowly in a natural process after subjective perception of LUTS. Therefore, along with age, the self-perception period (S-PP) of LUTS was considered as one of the most important risk factors for BPH [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%